If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 8 + -6 + 10 = -10 Reorder the terms: 8 + -6 + 10 + 5y = -10 Combine like terms: 8 + -6 = 2 2 + 10 + 5y = -10 Combine like terms: 2 + 10 = 12 12 + 5y = -10 Solving 12 + 5y = -10 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 5y = -10 + -12 Combine like terms: 12 + -12 = 0 0 + 5y = -10 + -12 5y = -10 + -12 Combine like terms: -10 + -12 = -22 5y = -22 Divide each side by '5'. y = -4.4 Simplifying y = -4.4
| 6(y+7)-11(y-6)= | | 2a+4=4 | | 12x-10=6x+30 | | 2+ln(x-5)=7 | | x^2-5*x+2=0 | | x^2-3*x+3=0 | | H(20)=11.00+0.07x | | y=180.38ln(1658)+1657.7 | | H(x)=11.00+0.07x | | y=180.38ln(x)+1657.7 | | =180.38ln(x)+1657.7 | | 0.8=40 | | 2m+6n+8m+5n= | | -2x-11=-7x-91 | | Z-1/3=8/3 | | Z-1/3=1/8 | | A-2=-8 | | 4c=50-2m | | 4x+0.5=0.25(x-3) | | x^0.5/0.5 | | 7z-1=4z+8 | | -0.3x+3=-114 | | 40in=ft | | 4c+2m=150 | | (9x-6w)+(4x+6y)+(2y+2w)= | | f(x)=5x+5 | | -6=z/3 | | -6=z/ | | -6n-2n= | | -8-3x=-29 | | -29+x=-52 | | -6(x-5)+3x=6-10(-3+x) |